Women’s Access to Places of Religious Worship in India: The Constitutional Conundrum of Gender Equality versus Freedom of Religion - Uma, Saumya (International Journal of Law, Human Rights and Constitutional Studies, 2022)
This paper examines how discrimination and exclusion of women from places of worship in India has been contested, and gender justice negotiated and asserted concretely by ordinary women. It examines three significant cases in this regard -the Shani Shingnapur case, the Haji Ali dargah case and the Sabarimala case. The paper also analyses the role of the judiciary in making inroads into patriarchal assertions of exclusion of women from places of religious worship, even as it attempts to balance the two sets of Constitutionally-guaranteed fundamental rights -right to equality and non-discrimination on the ground of sex, and freedom of religion and freedom to manage religious affairs. It briefly examines the varied responses of citizens’ group in support of and in opposition to women’s assertion for equality and nondiscrimination in accessing places of worship. In its conclusion, this paper delves briefly into narratives of culture, and explores the potential of a transformative cultural discourse that takes within its fold principles of equality, inclusion, dignity, respect, egalitarianism and social justice. It further examines the possibility of using ‘constitutional morality’ as a yardstick in addressing the conundrum. How to cite this article:  Singh M. Understanding Sexual Harassment at Workplace and its Redressal. Int Jour Law Hum Rights Const Stud 2020; 1(1&2): 8-12.